2020
DOI: 10.1128/msystems.00232-20
|View full text |Cite
|
Sign up to set email alerts
|

Integrating CRISPR-Enabled Trackable Genome Engineering and Transcriptomic Analysis of Global Regulators for Antibiotic Resistance Selection and Identification in Escherichia coli

Abstract: It is important to expedite our understanding of antibiotic resistance to address the increasing numbers of fatalities and environmental pollution due to the emergence of antibiotic resistance and multidrug-resistant strains. Here, we combined the CRISPR-enabled trackable genome engineering (CREATE) technology and transcriptomic analysis to investigate antibiotic tolerance in Escherichia coli. We developed rationally designed site saturation mutagenesis libraries targeting 23 global regulators to identify fitn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…To the best of our knowledge, this is the first report of the occurrence of the constitutively SoxR-activating mutation G121D in a clinical E. coli isolate, which so far had been described only in laboratory strains and Salmonella spp. (18,19,37). Mutations in the effector proteins MarA and SoxS were rare, except for S127N in MarA.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first report of the occurrence of the constitutively SoxR-activating mutation G121D in a clinical E. coli isolate, which so far had been described only in laboratory strains and Salmonella spp. (18,19,37). Mutations in the effector proteins MarA and SoxS were rare, except for S127N in MarA.…”
Section: Discussionmentioning
confidence: 99%
“…Chen and co-workers constructed mutant libraries according to the principle of rational design. First, 23 global regulators in E. coli were selected based on the literature and information available in databases . The functional residues were then selected, including DNA-binding domains, metal binding sites, dimerization domains, and so on.…”
Section: Emerging Engineering Technologies Provide Novel Opportunitie...mentioning
confidence: 99%
“…According to the intragenic mutation studies summarized by Conrad and Palsson, broad and systemic regulatory changes are found in ALE strains. Limited mutations in regulatory hubs can provide a large increase of fitness. , Furthermore, mutations in global regulators involved in transcription and translation can lead to a metabolic selection during an adaptation to complex environments. , Chen reported that 23 global regulators that can simultaneously alter the expression levels of many genes were targeted to construct mutant libraries and identify fitness-conferring mutations in response to diverse antibiotic stresses …”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Their outcomes represent a novel method to aid a better understanding of the mechanisms of resistance to aminoglycoside antibiotics and tetracycline antibiotics. It can also be utilized for quickly identifying resistance-related mutations [61].…”
Section: Identifying Functions Of Genes In Bacteriamentioning
confidence: 99%